EEG frontal asymmetry in the depressed and remitted elderly: Is it related to the trait or to the state of depression? - Carvalho, Alessandro; Moraes, Helena; Silveira, Heitor; Ribeiro, Pedro; Piedade, Roberto A.M.; Deslandes, Andréa C.; Laks, Jerson; Versiani, Marcio (Journal of affective disorders, 2011)
Over the last 30 years, frontal EEG asymmetry has been investigated with regards to the study of emotion, motivation, and psychopathology. We analyzed the frontal alpha asymmetry, depressive symptoms with a Beck Depression Inventory (BDI) and quality of life with a Short Form Health Survey-36® (SF-36®) in depressed ( n = 12), remitted ( n = 8) and non-depressed ( n = 7) elderly subjects. We also evaluated the correlation between the frontal EEG asymmetry and physical and mental aspects of SF-36®. The groups showed no difference regarding the frontal alpha asymmetry (F = 0.37; p = 0.69). Moreover, there was no significant correlation between frontal asymmetry and quality of life (mental and physical aspects). The results showed no evidence of a relationship between frontal asymmetry, quality of life and depression in the elderly. Future studies on frontal asymmetry should carefully consider the effects of age.